Contextualizing uncontrolled oil trade flows: A novel categorization. (November 2022) - Hatipoglu, Emre; Al-Suwailem, Majed; Muhsen, Abdel Rahman; Al Muhanna, Saleh
Abstract: Although states and international institutions have developed elaborate sets of laws and regulations to oversee the legal movement of oil, significant amounts of oil are moved out of controlled channels every year with considerable financial, political and security ramifications. Despite their salience for global political economy, scholarly analyses of uncontrolled oil movements are recent and scant. This paper aims to facilitate systematic analysis of uncontrolled oil movements around the globe by presenting a novel categorization. Our categorization relates the incentives of players involved, either as states or nonstate actors, to the capabilities these players possess when moving uncontrolled oil, either as buyers or sellers. Brief case analyses demonstrate that incentives of actors and capabilities they possess exhibit considerable variance. The nonstate actors we examine predominantly take advantage of arbitrage opportunities that borders and/or lapses in political authority create. States engaging in uncontrolled movement of oil in our cases, on the other hand, are rather motivated by an immediate need to create revenue or secure oil supplies for their economy or military. The state and nonstate actors in our analysis also tend to differ with respect to the reactions they give to changes in political and economic landscape. Nonstate actors emerge as agile actors that are quick to seize opportunities due to lapses in authority and more readily adapt to countermeasures. States can move oil at a larger scale due to their command over capital intensive equipment; however, they are more vulnerable to international scrutiny and coercive countermeasures. The insights from our analysis motivate further comparative, data-based research to identify causal processes leading to various forms of uncontrolled oil movements.